The EFFECT OF ORGANIC LEACHATE AND RICE WASHING WATER ON COMPOSTING TIME OF ORGANIC WASTE - Yahya, Husnawati; Rahman, Arief; Win Kuara, Rezeki (SEAMEO BIOTROP, 2024)
Waste is an integral part of human life. The increase in population is one factor that increases the waste generated. The more the population, the more activities are carried out. Organic leachate and rice washing water are environmentally friendly compost activators and are easily obtained from daily activities. Composting is a waste management strategy. Composting is an organic method through the activity of microorganisms to decompose natural materials into materials, including humus. The purpose of this study was to determine the moisture content, temperature, pH, C/N ratio, and macro nutrients during the composting process. The physical parameters of compost from the three activator concentrations showed that the treatment of P3 (with the addition of leachate formulation 20 ml/kg and rice washing water 15 ml/kg) and P2 (with the formulation adding 20 ml/kg leachate and 10 ml rice washing water), the physical compost were brownish black in color, fine textured and smelled of soil on the 22nd day. The P3 treatment has met the quality criteria of compost according to SNI 19-7030-2004, the moisture content (30%), temperature (27°C), pH (6,8), C-Organic (32,9%), Nitrogen (1,42%), Phosphor (0,65%) and Potassium (1,63%). For the C/N ratio, the result of all treatments did not meet the quality criteria of compost according to SNI 19-7030-2004. The C/N ratio of all treatments showed that it is still above the maximum standard that has been set at 20.